One Health Surveillance for Rabies: A Case Study of Integrated Bite Case Management in Albay Province, Philippines - Rysava, Kristyna; Espineda, Jason; Silo, Eva Angela V.; Carino, Sarah; Aringo, Ariane Mae; Bernales, Rona P.; Adonay, Florencio F.; Tildesley, Michael J.; Hampson, Katie (Frontiers in Tropical Diseases, 2022)
Canine rabies is a significant public health concern and economic burden in the Philippines. Animal Bite Treatment Centers (ABTCs) that provide post-exposure prophylaxis (PEP) to bite patients have been established across the country, but the incidence of bite patient presentations has grown unsustainably, whilst rabies transmission in domestic dogs has not been controlled. Moreover, weak surveillance leads to low case detection and late outbreak responses. Here we investigated the potential for Integrated Bite Case Management (IBCM) to improve rabies detection in Albay province. Using information obtained from animal bite histories combined with phone follow-ups and field investigations, we demonstrated that IBCM resulted in a fourfold increase in case detection over 13 months of study compared to the prior period. Bite patient incidence across Albay was very high (>600/100,000 persons/year) with PEP administered mostly indiscriminately. Clinic attendance reflected availability of PEP and proximity to ABTCs rather than rabies incidence (<3% of patient presentations were from “probable” or confirmed rabies exposures) and is therefore not a suitable indicator of rabies burden. Further analysis of the IBCM data suggests that rabies transmission is mostly localized with focal cases from the previous month and current cases in neighbouring villages being most predictive of future rabies occurrence. We conclude that investigations of suspicious biting incidents identified through IBCM have potential to foster intersectoral relationships, and collaborative investments between public health and veterinary services, enabling the One Health ethos to be applied in a more sustainable and equitable way. Triage of patients and investigations of suspect dogs offer an effective tool for improved PEP provisioning and reduction of unnecessary expenditure, whilst targeted field investigations should lead to increased and earlier detection of rabid dogs. Given the enduring risk of re-introductions from neighbouring populations, enhanced surveillance is critical to achieving and maintaining rabies freedom.